2004
DOI: 10.1097/00000542-200402000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Pneumonia

Abstract: The results suggest that early onset pneumonia leads to secondary injuries in head-injured patients. Nasal carriage of S. aureus, aspiration before intubation, and use of barbiturates are specific independent risk factors for early onset pneumonia and must be assessed to find and evaluate strategies to prevent early onset pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(59 citation statements)
references
References 29 publications
3
49
0
3
Order By: Relevance
“…Furthermore, our study expands these results to phagocytosis of live S. aureus, which is a predominant pathogen, especially in patients with brain trauma (9,10). More important, the results indicate substantial differences between the two barbiturates thiopentone and methohexitone with respect to their inhibitory potency and a differential pattern of inhibition.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, our study expands these results to phagocytosis of live S. aureus, which is a predominant pathogen, especially in patients with brain trauma (9,10). More important, the results indicate substantial differences between the two barbiturates thiopentone and methohexitone with respect to their inhibitory potency and a differential pattern of inhibition.…”
Section: Discussionsupporting
confidence: 64%
“…In this population, pneumonia usually occurs within the first four days of mechanical ventilation and is termed early-onset pneumonia (EO-VAP) [1]. The incidence of EO-VAP ranges from 21 to 60% [2, 3] in critically ill patients with traumatic brain injury (TBI) and is about 48% in those with subarachnoid hemorrhage. In a mixed population of patients in coma due to various causes, EO-VAP accounted for 70% of all cases of pneumonia [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among infections, pneumonia (PN) is a major cause of morbimortality [6], [7]. We [8] and others [9] have reported that methicillin-susceptible Staphylococcus aureus (MSSA) is the main pathogen involved in post-traumatic PN. A marked depression of cell-mediated immune function, known as post-traumatic immune suppression (IS), plays a role in sepsis after severe trauma [10].…”
Section: Introductionmentioning
confidence: 99%